2001
DOI: 10.1016/s0014-5793(01)02598-4
|View full text |Cite
|
Sign up to set email alerts
|

Disulfide bonds stabilize JC virus capsid‐like structure by protecting calcium ions from chelation

Abstract: To investigate the role of disulfide bonds in the capsid structure, a recombinant JC virus-like particle (VLP) was used. The major capsid protein, VP1, of the JC virus was expressed in yeast cells. The yeast-expressed VP1 was self-assembled into a VLP. Disulfide bonds were found in the VLP which caused dimeric and trimeric VP1 linkages as demonstrated by nonreducing SDS^PAGE. The VLP remained intact when disulfide bonds were reduced by dithiothreitol. The VLP without disulfide bonds could be disassembled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 32 publications
(54 reference statements)
0
36
0
Order By: Relevance
“…3C). Previous studies have demonstrated that disulfide bond-reducing agents expand BPV (15,21,29) and that disulfide bonds and calcium bridges stabilize polyomavirus virions (4,5,14). However, chelating and reducing agents did not enhance chaperone-mediated disassembly of either papilloma-or polyomavirus virions (data not shown).…”
Section: Hsp70 Chaperones Associate With Polyomavirus Virions Early Imentioning
confidence: 76%
See 1 more Smart Citation
“…3C). Previous studies have demonstrated that disulfide bond-reducing agents expand BPV (15,21,29) and that disulfide bonds and calcium bridges stabilize polyomavirus virions (4,5,14). However, chelating and reducing agents did not enhance chaperone-mediated disassembly of either papilloma-or polyomavirus virions (data not shown).…”
Section: Hsp70 Chaperones Associate With Polyomavirus Virions Early Imentioning
confidence: 76%
“…The carboxy terminus of L1 or VP1 mediates interpentameric contacts in the assembled capsid (13,16,17,22). These contacts are stabilized by disulfide bonds for papillomaviruses (15,21,29) or by both disulfide bonds and calcium bridges for polyomaviruses (4,5,14). …”
mentioning
confidence: 99%
“…Thus, VLPs are an efficient means of being about gene transduction. The major capsid protein, VP1, of JCV is able to selfassemble to form VLP when expressed in insect, 13,14 yeast, 16 and E. coli 15 without the presence of the other minor capsid proteins, VP2 and VP3. In this study, we found that VLP was able to package DNA in E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, JCV VP1 has been cloned and expressed in the baculovirus, 13,14 Escherichia coli, 15 and yeast. 16 The recombinant VP1 protein is able to self-assemble to form a virus-like particle (VLP). The characteristics of the VLP, such as its typical morphology, its binding to cells, internalization, and its transportation to nucleus are similar to native JCV virions 13 indicating that the JCV VLP has the potential to deliver foreign genes into susceptible cells for expression.…”
mentioning
confidence: 99%
“…This NLS of JCV VP1 was shown to be inefficient in mediating nuclear transport (16). However, JCV virus-like particles (VLPs) consisting exclusively of recombinant VP1 purified from either Escherichia coli or a baculovirus-insect cell expression system and assembled by the formation of disulfide bonds (17) were found to be transported to the nucleus of host cells (18,19). We have now investigated the mechanism of JCV nuclear entry with VLPs that exhibit both morphological characteristics and physiological functions, including hemagglutination activity, cell attachment, and cellular trafficking, similar to those of JCV virions (18 -20).…”
mentioning
confidence: 99%